Small sample sorting of primary adherent cells by automated micropallet imaging and release. Issue 7 (17th June 2014) - Shah, Pavak K.; Herrera‐Loeza, Silvia Gabriela; Sims, Christopher E.; Yeh, Jen Jen; Allbritton, Nancy L.
Abstract Primary patient samples are the gold standard for molecular investigations of tumor biology yet are difficult to acquire, heterogeneous in nature and variable in size. Patient‐derived xenografts (PDXs) comprised of primary tumor tissue cultured in host organisms such as nude mice permit the propagation of human tumor samples in an in vivo environment and closely mimic the phenotype and gene expression profile of the primary tumor. Although PDX models reduce the cost and complexity of acquiring sample tissue and permit repeated sampling of the primary tumor, these samples are typically contaminated by immune, blood, and vascular tissues from the host organism while also being limited in size. For very small tissue samples (on the order of 103 cells) purification by fluorescence‐activated cell sorting (FACS) is not feasible while magnetic activated cell sorting (MACS) of small samples results in very low purity, low yield, and poor viability. We developed a platform for imaging cytometry integrated with micropallet array technology to perform automated cell sorting on very small samples obtained from PDX models of pancreatic and colorectal cancer using antibody staining of EpCAM (CD326) as a selection criteria. These data demonstrate the ability to automate and efficiently separate samples with very low number of cells. © 2014 International Society for Advancement of Cytometry